Isolation and Characterization of Phosphate Solubilizing Diazotrophic Bacteria from Rhizosphere of Rice Plant of Indo-Nepal Border - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2016)
Free-living nitrogen fixing bacteria were isolated from the rhizosphere of rice plant of different regions of Indo-Nepal border. 33.78% isolates among them showed mineral phosphate solubilization. On the basis of bacterial characterization and identification with Bergey’s manual of Determinative Bacteriology (Holt et al, 1994), 38% isolates showed maximum similarity with Pseudomonas and Azotobacter, 30% with members of Enterobacteriaceae, 4% with Gram’s positive Microbacterium sp. and 28% was categorized unknown. ECI 12A isolate showed maximum solubilization index (S.I.), 0.809 on solid medium whereas 188.65 mg P/mg dry weight phosphate solubilization in liquid medium. The highest phosphate solubilizing isolate ECI 12A was sequenced after amplification of partial 16S rRNA gene, blast with BLASTn 2.2.17 program of NCBI showed 99 % identity having 99 % query coverage with Microbacterium sp. This isolate has been named as Microbacterium sp. Strain ECI-12A.The sequence of this strain has been deposited in NCBI Gene Bank under accession number EU155122 and this strain has promising potential for developing as a plant growth promoting rhizobacteria (PGPR) as well as biofertilizer. Academic Voices Vol.5 2015: 79-87